Evaluation of the polymorphism of the GDF9 and BMP15 genes and their relationship with the reproductive functions of sheep of different breeds - Z. K. Gadzhiev; E. S. Surzhikova; D. D. Evlagina; A. I. Surov; S. N. Shumaenko (Юг России: экология, развитие)
Aim. Polymorphism is the result of evolutionary processes and is inherited, associated with biodiversity and modified by natural selection and functions to preserve various forms of population. It is economically advantageous to find genes that can be used in breeding in such a way as to increase the fertility of animals in different natural geographical zones, since the adaptive abilities of organisms are complicated. In this regard, the purpose of this study was to study the genetic potential of sheep of different breeds bred in various ecological and geographical regions of the North Caucasus with pasture-pasture and pasture-stall conditions of sheep breeding.Material and Methods. Genotyping was undertaken of sheep of different breeds contained in various natural and climatic zones of the Republic of Dagestan and the most arid region of Stavropol Territory in the zone of risky agriculture where the climate is sharply continental. Genotyping in the loci of the genes of differential growth factor (GDF9) and bone morphogenetic protein (BMP15) was carried out by PCR-PDRF (polymorphism of the lengths of restriction fragments) by cutting DNA using endonuclease restriction and further analysis of the size of the resulting PCR fragments. The genetic structure of genes has been studied by methods of genetic and statistical analysis of the data obtained.Conclusion. The genetic structure of sheep populations of different breeds bred in the foothills of the Republic of Dagestan and the arid region of Stavropol Territory was studied for the first time. Information obtained on the role of the degree of genetic variability of sheep of different breeds provides data which can contribute to the ecological well-being of herds and the status characterising the signs of multiple birth rates is also determined. This will further improve and significantly accelerate breeding work with livestock, since an important task of further increasing the efficiency of the industry is the reproduction of the herd together with a simultaneous increase in the productivity of animals.